2015
DOI: 10.1177/0003319715578565
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention Rates and Associated Independent Predictors for Progression of Nontarget Lesions in Patients With Diabetes Mellitus After Drug-Eluting Stent Implantation

Abstract: Little is known about clinically driven percutaneous coronary intervention (PCI) rates and predictors for progression of nontarget lesions in diabetic patients who have undergone drug-eluting stent (DES) implantation. We retrospectively analyzed the clinical and angiographic data of 2187 diabetic patients undergoing DES implantation. The cumulative rate of nontarget lesion PCI was 6.3% at 1 year, 14.3% at 2 years, and 19.8% at 3 years. The independent predictors of need for clinically driven PCI in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Moreover, Turakde et al [27] demonstrated that a preprocedural serum UA level exceeding 5.5 mg/dL was a robust and significant prognostic factor for ISR in individuals diagnosed with stable or unstable angina pectoris. Similarly, Wang et al [28] revealed that among diabetic patients, each 50 μmol/L increase in pre-procedural serum UA level significantly correlated with endothelial restenosis following successful placement of DES.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, Turakde et al [27] demonstrated that a preprocedural serum UA level exceeding 5.5 mg/dL was a robust and significant prognostic factor for ISR in individuals diagnosed with stable or unstable angina pectoris. Similarly, Wang et al [28] revealed that among diabetic patients, each 50 μmol/L increase in pre-procedural serum UA level significantly correlated with endothelial restenosis following successful placement of DES.…”
Section: Discussionmentioning
confidence: 89%
“… 26 Restenosis is one of the major long-term complications of PCI in such patients. 27 , 28 Nonetheless, the correlation between diabetes and in-stent restenosis is not well documented. 29 , 30 A cohort study on patients with chronic total occlusion indicated that the post-PCI complication rate was the same in diabetics and nondiabetics.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] The onset of new lesions was not included because previous study showed that more than 95% of re-vascularization in non-target lesions was driven by preexisting lesions rather than new onset lesions. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%